PERANAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN KARAKTER SISWA DI SMAN 2 BANDAR - Aris Firjatullah Pratama; Sri Wahyuni Silalahi (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this research is to see what kind of character strengthening can build students' character based on the value of Islamic education. This research uses descriptive qualitative research and also quantitative research at SMAN 2 Bandar with data collection techniques of observation, interviews with teachers/principals. and accurate documentation based on valid data. In addition, the data is presented using a descriptive approach in the form of written words to clarify the data collected and analyzed. Character education models must be developed in schools based on religious education to make religious education the main subjects used to build student character. Religious education must teach religious attitudes and behavior. Another important aspect that needs to be considered in the framework of effective character building in schools is the vision, mission and goals of the school and togetherness. There is a program. clear and detailed covering all subjects and all teachers. There is support for facilities and special teams for the implementation of student character development programs..